The militarization of prayer in America: White and Native American spiritual warfare - McAlister, Elizabeth A. (Journal of religious and political practice, 2016)
This article examines how militarism has come to be one of the generative forces of the prayer practices of millions of Christians across the globe. To understand this process, I focus on the articulation between militarization and aggressive forms of prayer, especially the evangelical warfare prayer developed by North Americans since the 1980s. Against the backdrop of the rise in military spending and neoliberal economic policies, spiritual warfare evangelicals have taken on the project of defending the United States on the "spiritual" plane. They have elaborated a complex theology and prayer practice with a highly militarized discourse and set of rituals for doing "spiritual battle" and conducting "prayer strikes" on the "prayer battlefield". The work draws on ethnographic fieldwork at an intensive spiritual warfare boot camp organized by a group of Native Americans who have founded a training base in Oklahoma dedicated to training recruits in the theology and practical strategy of spiritual warfare. Despite their hyper-aggressive rhetorical and ideological stance, members of this network in fact practice self-sacrificial rituals of fasting, holiness, and submission to the Holy Spirit. Native prayer warriors are using spiritual warfare prayer to assert a privileged place for themselves in Christian life as heirs of God's authority over the stewardship of North American land and as central to the project of repairing sinful pasts both on and off the reservations, reconciling present racial conflict, and defending the land in spiritual battle against new immigrant invasions by foreign, demonic forces.